2020
DOI: 10.1177/0042098019892582
|View full text |Cite
|
Sign up to set email alerts
|

Explaining transit expenses in US urbanised areas: Urban scale, spatial form and fiscal capacity

Abstract: This research seeks to explain patterns of capital investment and operating expenses for urban transit systems in the United States. We isolate supply factors including urban scales, urban spatial form and financial capacity. Individual and group transit demands are accounted for by social and demographic characteristics including education level, immigrant populations, poverty levels, senior population and race. The results demonstrate that transit investments are super-linear to population, directly contradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Under the influence of this unique economic structure, local governments also have a greater responsibility for the provision of local public services and the construction of infrastructure. Urban areas with higher population density ensure sufficient tax revenues by making earmarked and comprehensive regulations and policies to invest in infrastructure construction for the future (a sign of rapid urbanisation) or preferential treatment by the central government to selected areas (intergovernmental fiscal relations) (Hannay and Wachs, 2007; Zhao et al, 2021). In this way, basic infrastructure and public services in large cities are more generally accessible, with super-linear behaviours presenting as the products of government decision-making (Meirelles et al, 2018).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Under the influence of this unique economic structure, local governments also have a greater responsibility for the provision of local public services and the construction of infrastructure. Urban areas with higher population density ensure sufficient tax revenues by making earmarked and comprehensive regulations and policies to invest in infrastructure construction for the future (a sign of rapid urbanisation) or preferential treatment by the central government to selected areas (intergovernmental fiscal relations) (Hannay and Wachs, 2007; Zhao et al, 2021). In this way, basic infrastructure and public services in large cities are more generally accessible, with super-linear behaviours presenting as the products of government decision-making (Meirelles et al, 2018).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Expenditures on transit show are insignificant or (weakly) significant and negative. This is in line with the insignificant effects found for subways in other work (Gonzalez-Navarro & Turner, 2018;Zhao, Lou, Fonseca, Feiock, & Shen, 2020). However, positive Tiebouteffects are also commonly found for transit, especially in China (Dai, Bai, & Xu, 2016;Li et al, 2019;Zhang et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Traditionally in the literature, the public sets the demand for public goods that will benefit them. Empirical studies demonstrated that the demographics of demanders, their socioeconomic status, and political ideology can significantly affect policy choices (Feiock et al, 2008;Hawkins 2014;Tong et al;Zhao et al). Demanders can express their support for officials through votes, contributions, or other instrumental political resources.…”
Section: Demandsmentioning
confidence: 99%